2016
DOI: 10.1186/s12978-016-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain and its associated factors in Harari Regional State: Institution based cross-sectional study, Eastern Ethiopia

Abstract: BackgroundGestational weight gain is an important factor that supports optimal outcome for mothers and their infant. Whereas women who do not gain enough weight during pregnancy have a risk of bearing a baby with low birth weight, those who gain excessive weight are at increased risk of preeclampsia and gestational diabetes. Nonetheless, data on gestational weight gain and its determinants are scarce in developing countries, as it is difficult to collect the information throughout the pregnancy period. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 17 publications
3
67
0
1
Order By: Relevance
“…Similar results were reported in Ghana, where the estimated prevalence of low GWG based on the GWG over the whole pregnancy according to IOM guidelines was 62.7%, and the percentage of women with GWG less than the third centile of GWG according to the INTERGROWTH‐21st standards was 27% (Adu‐Afarwuah et al, ). In Ethiopia, the prevalence of low GWG based on the total GWG according to the IOM criteria was also high (69.3%; Asefa & Nemomsa, ). Given the adverse maternal and child health outcomes associated with low GWG, our findings indicate that low GWG is a concern in the study area and highlights the need for effective maternal health and nutrition interventions to influence these outcomes (Hamad, Cohen, & Rehkopf, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported in Ghana, where the estimated prevalence of low GWG based on the GWG over the whole pregnancy according to IOM guidelines was 62.7%, and the percentage of women with GWG less than the third centile of GWG according to the INTERGROWTH‐21st standards was 27% (Adu‐Afarwuah et al, ). In Ethiopia, the prevalence of low GWG based on the total GWG according to the IOM criteria was also high (69.3%; Asefa & Nemomsa, ). Given the adverse maternal and child health outcomes associated with low GWG, our findings indicate that low GWG is a concern in the study area and highlights the need for effective maternal health and nutrition interventions to influence these outcomes (Hamad, Cohen, & Rehkopf, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gestational weight gain (GWG) is a complex biological phenomenon that influences pregnancy outcomes (IOM and NRC, ). An appropriate GWG is essential for optimal pregnancy outcomes for both the mother and her infant (Asefa & Nemomsa, ). Low GWG is associated with adverse outcomes including low birth weight (LBW; Edwards, Hellerstedt, Alton, Story, & Himes, ; Hellerstedt, Himes, Story, Alton, & Edwards, ; Hickey, McNeal, Menefee, & Ivey, ; Schieve, Cogswell, & Scanlon, ), intrauterine growth restriction (Strauss & Dietz, ), small for gestational age (SGA; Hellerstedt et al, ; Hickey et al, ; Nielsen, Gittelsohn, Anliker, & O'Brien, ), and preterm delivery (Hickey, Cliver, Goldenberg, McNeal, & Hoffman, ; Stotland, Cheng, Hopkins, & Caughey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Desirable gestational weight gain (GWG) supports the increased metabolic demands required for positive pregnancy outcomes [1]. Guidelines regarding appropriate levels of GWG have been promoted worldwide [2]. A variety of guidelines about the GWG exist; their approach in GWG management also varies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of weight gained during pregnancy is determined by factors including the mother's age [2,6,7], parity [2,6,7], income status [2,8], educational status [7], social class [6], and pre-pregnancy maternal weight [2,9]. Other factors include antenatal care (ANC) [2,6], physical activity during pregnancy [10] and perinatal depression [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous regional studies have investigated the level of physical activity, ANC service utilization in pregnancy, the timing of ANEx, antenatal depression, and gestational weight gain [22,23]. Most of them reported that many Ethiopian pregnant women are keen on exercise participation but don't practice regular physical exercise, which makes the question about the in uence and belief of antenatal exercise on mother and fetal health more important [8,24,25].…”
Section: Introductionmentioning
confidence: 99%